A Study on Identification of Significant Environmental Aspects and Impacts of Piling and Foundation Works - T.S, Tuan Fadzilah; Mahmood, Noor Zalina; Che Hassan, Che Rosmani (Malaysian Journal of Science, 2008)
The construction sector, which can contribute to a nation's economic growth is vital for the development of any nation. Improper management and poor control measures in this sector could lead to negative impacts to the environment such as air pollution, noise pollution, dust problem; solid and hazardous waste disposal and human health. Therefore this study was undertaken to identify significant environmental aspects and impacts of piling and foundation works, which is an early phase for any construction project. Identification of environmental aspects and impacts is very important in decision making to reduce the risk and possible impact at early stage of a construction process. Significant environmental aspects and impacts were identified using both qualitative and quantitative methods [1]. There were thirty one (31) environmental aspects from filing and foundation works identified. The most significant aspects were the activities from the drilling process, transportation, machinery activities and generator set (gen set) operation. Mitigations measures were identified which involved sediment control, equipment fuels and lubricants control and air pollution control. The mitigation measures are important to help the construction sector manage their activities in minimizing any potential impacts.